Contextual Evangelism among Muslim Refugee Communities: A Case Study of Sudanese International Church in Amman, Jordan - Mey, Sioe; Astuti, Tri (Shift Key : Jurnal Teologi dan Pelayanan, 2025)
This study explores the challenges of evangelism at the Sudanese International Church in Amman, Jordan, located within a predominantly Islamic socio-cultural context. The research aims to identify and analyze effective evangelistic methods applied by church workers among Middle Eastern refugee communities. Using a qualitative descriptive approach, data were collected through in-depth interviews and field observations. The findings reveal that effective evangelism in Jordan requires relational, holistic, and contextual approaches. The integration of the Three Circles method, the Markaz discipleship model, and social acts of love forms a strategic framework for reaching Muslim and refugee communities. The novelty of this research lies in its synthesis of theological and socio-humanitarian approaches, providing a practical model for Christian mission in Islamic contexts